Effect of different adhesive systems on microleakage in class II composite resin restorations - Mauro, Silvio José [UNESP]; Durao, V. C. A. [UNESP]; Briso, André Luiz Fraga [UNESP]; Sundefeld, Maria Lúcia Marçal Mazza [UNESP]; Rahal, V. [UNESP] (Elsevier B.V., 2012)
The success of a restoration depends on the interaction between the adhesive system and the dental substrate. The aim of this study was to evaluate the occurrence of microleakage in class II resin restorations using different adhesive systems light cured in enamel and dentin: conventional and self-etching acrylic. For that purpose 40 human molars were sectioned in buccal-lingual direction, making up 80 samples (40 mesial and 40 distal halves). Each sample had cavities class II prepared and the occlusal margins were kept in enamel while the cervical margins were kept in dentin. The specimens were divided into four groups (n=20) according to the adhesive system used. After restorative and thermocycling procedures the degree of dye leakage was qualified using a stereomicroscopic loupe (45X). Data were analyzed by ANOVA and Kruskal-Wallis tests (alpha=0.05). Results obtained for occlusal (enamel) and cervical (dentin) margins (pm) were, respectively: GI-11.45, 20.7; GII-15.4, 19.4; GIII-23.3, 24.05; GIV-31.85, 17.85. In enamel, the self-etching adhesive systems presented the less control of marginal leakage in the occlusal and cervical margins. Although for the dentin there was no difference among the adhesive systems used. It was concluded that no adhesive system hermetically sealed the restorations with cavity margins in enamel or dentin and self-etching adhesives did not improve microleakage controlling when compared to conventional systems. (c) 2012 Elsevier Ltd. All rights reserved.
Keywords: Composites; Biological adhesion; Microscopy